Melvin Mencher's News Reporting and Writing - Melvin Mencher (McGraw-Hill Co, 2006)
Jil.1 = NRW Plus Student berisi : The reporter at work, the basics, writing the story, reporting new rwlease, from accident to education, dll Jil.2 = Brush Up Student berisi Diagnotic exercises, grammar, funtuation, spelling, style, journalistic practice, dll